Reforms of the Political System and Constitutional Government Regulation: Harmonisation or Collisions? - Avakian, S. (Bulletin of Yerevan University C: Jurisprudence, 2019)
Political practices of several post-Soviet states prompts a discussion that the constitutional state reforms may touch upon problems that can be resolved fairly peacefully, as well as problems causing vigorous participation of the people. With different levels of rapidness, all post-Soviet states allowed multiplicity of parties, covered private ownership in the basic laws, established constitutional control bodies. But when the questions of a style of ruling and a political regime emerged, it became obvious that it barely relates to a constitutional law (i.e., state) reform. And political calamity, called colour-coded revolutions, commenced. We should add one question of the mechanism for constitutional changes which is far reaching and not quite procedural. Unfortunately, many forces take as a premise that the constitutional rules imposed under their direction should be almost perpetual and 22 cannot be reformed. And then a sophisticated route towards constitutional reforms is selected. It is almost apparent that states should favour peaceful routes towards constitutional state reforms that are accessible to political forces and the people. This would bolster a precise answer to the following question: what do we achieve when making the relevant constitutional and political steps, - harmony of regulation and society or collision? Trying to sum up, a positive constitutional normative regulation should be enriched with such social and public features as rigidity of state power and state discipline, transparency and responsibility of government towards the people, the service of ownership to the benefit of the person and the state, state’s care over the person and citizen’s responsibility to assist the state in its public affairs, democratisation of civic life, timely reinforcement of rights and freedoms in response to society’s needs and scientific and technological progress, self-responsibility of the individual, respect towards everyone’s dignity.
Keywords: reforms, constitutional regulation, state power, responsibility